Perkembangan Sistem Pertahanan/Keamanan Siber Indonesia dalam Menghadapi Tantangan Perkembangan Teknologi dan Informasi: - - Makbull Rizki (Talenta Publisher, 2022)
The challenges in the world of defense and security are always dynamic, always changing in form, nature, and source of the threat itself. In the previous era, the challenges of defense and security were form by direct attacks with war equipment and involving more intense physical contact, while in the era of technology and information which is developing rapidly, security and defense challenges have created a new dimension, namely cyber security. This article will describe how cyber threats and attacks are a challenge for the world of defense in this current era, and how is the development of Indonesia's current cyber defense and security system.